Burden of respiratory syncytial virus disease in infants and the potential value of maternal immunization in Greece - Gourzoulidis, George; Solakidi, Argyro; Markatis, Eleftherios; Detsis, Marios; Siahanidou, Tania; Dimitriou, Gabriel; Charitou, Antonia; Tzanetakos, Charalampos; Mendes, Diana; Barmpouni, Myrto (Frontiers in Public Health, 2025)
ObjectiveThe objective was to assess the burden of respiratory syncytial virus (RSV) and evaluate the cost-effectiveness of maternal vaccination using the bivalent RSV prefusion F-protein (RSVpreF) vaccine to prevent RSV infections among Greek infants.MethodsA Markov model was adapted from the perspective of a public payer to simulate the health and economic outcomes of RSV from birth to 1 year of age. Key inputs for the model, including vaccine efficacy, utility values, epidemiological data, and direct medical costs [prices in euros (€), 2024], were obtained from official sources. Model main outcomes were medically attended RSV cases, RSV-related deaths, quality-adjusted life-years (QALY) gained, direct medical costs and incremental cost-effectiveness ratios (ICER).ResultsThe model analysis estimated that the annual number of RSV medically attended cases would be 21,935, with 22% requiring hospitalization, 32% managed in the emergency department (ED), and the remaining cases treated in outpatient settings. Furthermore, 11 RSV-related deaths were estimated. These cases represent a significant economic burden, with direct medical costs of €26 million. With a year-round maternal RSVpreF vaccination coverage of 19.5%, over 1,200 RSV medically-attended cases could be prevented annually. Vaccination benefits translated to 31 additional QALYs compared with no vaccination. Thus, the model analysis indicated that RSVpreF vaccination is a cost-effective strategy, resulting in an ICER of €8,280 per QALY gained compared to no vaccination.ConclusionAdministering maternal RSVpreF vaccination year-round can provide protection to infants against RSV from birth. From a payer perspective, maternal RSVpreF vaccination has been evaluated as a cost-effective alternative compared to no intervention, underscoring its value as a preventive strategy against RSV in Greece.